DEVELOPING LEARNERS WRITING SKILLS IN FOREIGN LANGUAGES (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
Developing writing skills is one of the most important aspects of learning a foreign language. It is crucial for learners to be able to effectively communicate their ideas and thoughts in writing, as writing is a key tool for conveying information and expressing oneself. In this article, we will dispute how to be a good foreign language writer, and outline seven ways we can enhance our foreign language writing skills.